2017
DOI: 10.1016/j.jece.2017.08.041
|View full text |Cite
|
Sign up to set email alerts
|

New operational mode of an electrochemical reactor and its application to the degradation of levofloxacin

Abstract: The flow-by electrochemical reactor is generally used in batch mode with extended process time in order to achieve high efficiency in the removal of organic contaminant from aqueous solution. Moreover, the batch mode system is inappropriate for the treatment of wastewater in high volume or as a continuous stream. This paper presents a new operational mode for the electrochemical reactor in which the electrolyte passes over the electrodes just once at a reduced flow rate and with high hydraulic retention time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 51 publications
1
11
0
1
Order By: Relevance
“…As demonstrated in the literature, through the application of carbon-based cathode materials, O 2 is easily reduced to H 2 O 2 via the transfer of two electrons at a potential of 0.682 V vs SHE , Some studies reported in the literature have pointed out different ways to improve the production of H 2 O 2 through ORR via the 2-electron pathway; some of these ways include the following: Improvement of the catalytic properties of the cathode; this can be done by studying and developing new highly efficient cathode materials based on carbon black (CB) or through the addition/doping of organic or inorganic catalysts into carbonaceous materials; ,, Improvement of oxygen supply in the electrochemical cell since the low solubility of oxygen in the cell causes the efficiency of the process to be controlled by diffusion. As reported in the literature, to help tackle this problem, some important progress has been made by performing the electrochemical operation under high pressure and at low temperature so as to improve oxygen solubility. ,, optimizing the shape/configuration of carbon-based cathodes by employing gas diffusion electrodes (GDEs) in flow-by electrochemical reactors instead of flow-through electrode reactors. ,,, the design of more efficient electrochemical reactors with enhanced turbulence. ,, …”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in the literature, through the application of carbon-based cathode materials, O 2 is easily reduced to H 2 O 2 via the transfer of two electrons at a potential of 0.682 V vs SHE , Some studies reported in the literature have pointed out different ways to improve the production of H 2 O 2 through ORR via the 2-electron pathway; some of these ways include the following: Improvement of the catalytic properties of the cathode; this can be done by studying and developing new highly efficient cathode materials based on carbon black (CB) or through the addition/doping of organic or inorganic catalysts into carbonaceous materials; ,, Improvement of oxygen supply in the electrochemical cell since the low solubility of oxygen in the cell causes the efficiency of the process to be controlled by diffusion. As reported in the literature, to help tackle this problem, some important progress has been made by performing the electrochemical operation under high pressure and at low temperature so as to improve oxygen solubility. ,, optimizing the shape/configuration of carbon-based cathodes by employing gas diffusion electrodes (GDEs) in flow-by electrochemical reactors instead of flow-through electrode reactors. ,,, the design of more efficient electrochemical reactors with enhanced turbulence. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutical products are one of the most interesting and representative examples, with thousands of compounds that have already been detected in natural aquatic environment up to the order of µg / L [4]. The occurrence of these substances in the environment is associated to their consumption by humans and animals for the treatment of various diseases and to the low efficiency of conventional wastewater treatment plants in their removal [5,6].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 The antibiotics as chemical compounds are vital components in several human medicines as well as veterinary practice, and their discharges into surface or groundwater supplies show hazardous side effects even at very low concentrations. 2 4 …”
Section: Introductionmentioning
confidence: 99%
“…The wide detection of the biologically active compound as the commonly used antibiotics in the water resources was classified as one of the essential concerns for the water, environmental, and health authorities in the world. , The antibiotics as chemical compounds are vital components in several human medicines as well as veterinary practice, and their discharges into surface or groundwater supplies show hazardous side effects even at very low concentrations. …”
Section: Introductionmentioning
confidence: 99%